My cousin Vinny - Launer, Dale; Launer, Dale; Schiff, Paul; Lynn, Jonathan; Pesci, Joe 1943-; Tomei, Marisa 1964- (Twentieth Century Fox Film, 1992)
In this must-see comedy hit, two carefree pals travelling through Alabama are mistakenly arrested and charged with murder. Fortunately, one of them has a lawyer friend in the family-Vincent Gambini, a former auto mechanic from Brooklyn who has never been in court-or in Alabama. When cousin Vinny arrives with his leather-clad girlfriend to handle his first case. it's real shock - for him and the Deep South!